“This cannot be its meaning in the mouth of the judge” (The case for the new English language translation of Alf Ross”™s On Law and Justice forthcoming on Oxford University Press) - HOLTERMANN, Jakob (Utopía y Praxis Latinoamericana, 2016)
The second English edition of Alf Ross”™s Â main work On Law and Justice is forthcoming on theÂ Oxford University Press. Instead of simply reprinting theÂ existing English language translation from 1958 the newedition contains a full new translation. This article by theÂ editor of the new edition unfolds the argument for thisÂ choice. This argument focuses on the highly negativeÂ role of H.L.A. Hart”™s influential critique for the receptionÂ of Ross”™s work in Anglo American legal philosophy.Â It claims, first of all, that Hart”™s critique essentiallyÂ misses the mark, and that it is ultimately a straw man.Â It further argues that even though Hart was at leastÂ partly responsible for this misreading the 1958 EnglishÂ translation certainly did not help. Due to a numberÂ of errors, omissions and problematic terminologicalÂ choices the first translation can be said to at least inviteÂ the inattentive or uncharitable reader to arrive at the kind of misreadings Hart arrived at.